Potential of Nile Tilapia (Oreochromis niloticus) as an Alternative Complementary Food Ingredient for Stunting Children - Nuryanto, Nuryanto; Afifah, Diana Nur; Sulchan, Mohammad; Martosuyono, Pujoyuwono; Ihsani, Kholifiyah; Kurniastuti, Permata Laila (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUNDS:The Result of the Basic Health Research 2018 stunting prevalence in Indonesia is 30.8%. One of the potential local foodstuffs in Indonesia is nile Tilapia fish (Oreochromis niloticus). Nile Tilapia fish has a high nutrient content, especially protein, calcium and monounsaturated fatty acids. OBJECTIVES: Analyzed of nutrient content and heavy metal content of lead in Nile Tilapia. METHODS:The study was a laboratory study using raw materials of Nile Tilapia fish . Then analyzed the content of proximate, fatty acids, amino acids and lead heavy metals. Statistical tests use descriptive tests. RESULTS:The total protein content of 18.46 grams, and the calcium content of 74.38 grams in 100 grams of material. Total fatty acids of Nile Tilapia 30.39%, Palmitic acid 7.87%, stearic acid 4.30%, oleic acid 8.13%, Linoleic Acid 3.67% of total fatty acids. Total amino acids is 21.56%, Arginine 1.88%, Leucine 1.69%, Lysine 1.84%, Aspartic Acid 2.16%, Glutamic Acid 3.45% of the total amino acids. CONCLUSION:High nutrient content in Nile Tilapia are proteins, calcium, oleic fatty acids, palmitic, linoleic and stearic acids. The highest amino acids are aspartic acid, glutamic acid, lysine arginine and leucine.